Multifunctional scaffolds of β-tricalcium phosphate/bioactive glass coated with zinc oxide and copper oxide nanoparticles - Oliveira, Rodrigo L.M.S.; Barbosa, Lucas; Pereira, Thaís C. [UNESP]; Dona, Luísa R.M.; Tabuti, Thiago G.; Tada, Dayane B.; Triboni, Eduardo R.; de Oliveira, Luciane D. [UNESP]; Trichês, Eliandra S. (Elsevier, 2024)
Incorporating nanoparticles into scaffolds with regenerative potential is a promissory strategy to provide them with antimicrobial activity. Bioceramics, such as β-tricalcium phosphate (β-TCP) and bioactive glasses (BGs), stand out among synthetic materials for bone regeneration. In this context, we report the incorporation of zinc oxide (ZnO) and copper oxide/copper nitrate (CuO/Cu2H3NO5) nanoparticles onto the surface of the β-TCP/BG scaffolds. This report addresses the physicochemical characterization of the scaffolds, their antimicrobial activity, and their response to MC3T3-E1 cells. Our findings show that the incorporation of both nanoparticles effectively inhibited S. aureus growth, including its biofilm formation. While the presence of the nanoparticles initially decreased MC3T3-E1 cell viability, cell proliferation improved with prolonged incubation. Overall, the β-TCP/BG_Zn and β-TCP/BG_Cu scaffolds showed an early antimicrobial response, aiding infection eradication, while also supporting cell proliferation over time.
Keywords: 3D printing; Antimicrobial activity; Copper nanoparticles; MC3T3-E1 cells; Multifunctional scaffolds; Zinc oxide nanoparticles